Cytotoxic Effect of Rosmarinus officinalis L. Leaf Extracts on Tumor Cell Line - Salih, Shahlaa M; Alobaidi, Khalid H; Alobaidi, Zinah F (Al-Nahrain Journal of Science, 2018)
This study was conducted to evaluate antitumor effects of roesmarinus (Rosmarinus officinalis) extracts (aqueous and methanol) on Rhabdomyosarcoma; RD cell line and a normal cell line; mouse embryo fibroblast; MEF). Chemical detections of Rosemary extracts revealed that the aqueous and methanol extracts were positive for flavonoids, alkaloids, phenol, terpenes, saponine, glycosides, steroids and tannins. The percentage growth inhibition (PGI) of five leaf extract concentrations 50, 100, 250, 500 and 1000 (µg/ml) were assessed in vitro using RD and MEF. The results revealed that the five concentrations of the plant extracts showed anti-tumor properties in a concentration-dependent manner, and the methanol extract recorded better values of PGI than aqueous extract in RD cell lines, while, less PGI values were recorded in the MEF cell line. This experiment investigated the cytotoxic activity of the methanolic and aqueous extracts of Rosemary at concentrations (50 -100 -250 -500 -1000 μg/mL) on RD cell lines. A dose-dependent reduction was observed in treated cell line after 24 hrs. of treatment, but lower concentrations exhibited lower cytotoxic effects. Maximum inhibition of proliferation was achieved at the highest concentration (1000 μg/mL).